DEVELOPING A PLUGIN TO PROTECT AGAINST VIRUS INFORMATION - Ulianovska, Yu. V; YakovenkoV. О.; Yakovenko, T. Yu.; Riabovolenko, V. A. (Systems and Technologies, 2023)
With the development of information and communication technologies and the implementation of the Internet in the almost all spheres of social life, the problem of dissemination and penetration of inappropriate content, which could cause both moral and material harm to users, arises. One of the ways to solve this problem is to filter the content coming to the user. This leads to the scientific and practical issue of developing a content filtering system on the Internet, as well as the applied software to implement this task. The significance of this issue determines the relevance of this research. The paper is related to the development of a software that checks the text content of the Web in order to identify potentially dangerous resources and protect users from unwanted information.